2021
DOI: 10.1088/1361-6528/abfee7
|View full text |Cite
|
Sign up to set email alerts
|

Pulsed laser-induced dewetting and thermal dewetting of Ag thin films for the fabrication of Ag nanoparticles

Abstract: Two different dewetting methods, namely pulsed laser-induced dewetting (PLiD)—a liquid-state dewetting process and thermal dewetting (TD)—a solid-state dewetting process, have been systematically explored for Ag thin films (1.9–19.8 nm) on Si substrates for the fabrication of Ag nanoparticles (NPs) and the understanding of dewetting mechanisms. The effect of laser fluence and irradiation time in PLiD and temperature and duration in TD were investigated. A comparison of the produced Ag NP size distributions usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 49 publications
6
11
0
Order By: Relevance
“…The morphology of both the undewetted Au­(2.6 nm)­Ag­(2.5 nm) (Figure a) and Ag­(2.3 nm)­Au­(2.3 nm) (Figure g) films shows bicontinuous structures, indicating Volmer–Weber growth in which thin film growth proceeds through the formation of nanoislands . Similar thin film morphologies have been reported for both Au and Ag films individually. At 80 °C (Figure b,h), both bilayer films show deepening of the grain boundaries and initiation of voids.…”
Section: Resultssupporting
confidence: 75%
See 3 more Smart Citations
“…The morphology of both the undewetted Au­(2.6 nm)­Ag­(2.5 nm) (Figure a) and Ag­(2.3 nm)­Au­(2.3 nm) (Figure g) films shows bicontinuous structures, indicating Volmer–Weber growth in which thin film growth proceeds through the formation of nanoislands . Similar thin film morphologies have been reported for both Au and Ag films individually. At 80 °C (Figure b,h), both bilayer films show deepening of the grain boundaries and initiation of voids.…”
Section: Resultssupporting
confidence: 75%
“…The thermal dewetting of single-layer Au and Ag along with Pt on SiO 2 /Si substrates has been studied in detail in our previous work. , It was found that void growth started right above the Hüttig temperature of the metal and complete dewetting into isolated NPs occurred at a temperature in between the Hüttig and Tammann temperatures, the temperatures at which the surface and bulk atoms in the metal become mobile, respectively. Considering the values of the Hüttig and Tammann temperatures for Ag (97 and 344 °C) and Au (128 and 396 °C), the effect of temperature on the dewetting of Au–Ag bilayer thin films was studied in the range of 80–450 °C at a fixed time of 30 min.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Before sputtering, the phosphorous-doped n -type Si (100) wafers with a resistivity of 1–20 Ω cm (Wafer World Inc., West Palm Beach, FL, USA) were cleaned successively with acetone, ethanol, and methanol, and dried using high-purity N 2 gas (99.999%, Praxair). Details of thermal dewetting to make metal NPs were described previously [ 36 , 37 , 38 ]. Briefly, thermal dewetting of 2.9 nm thick Au films on Si substrates was carried out in vacuum (~2 × 10 −3 Torr) at 600 °C for 1 h.…”
Section: Experimental Methodsmentioning
confidence: 99%